2020
DOI: 10.1123/tsp.2019-0087
|View full text |Cite
|
Sign up to set email alerts
|

The Birth of the Stars: A Participatory and Appreciative Action and Reflection Investigation into the Leadership and Development of a New Superleague Netball Club

Abstract: This Participatory and Appreciative Action and Reflection (PAAR) investigation illustrates a leader’s first steps in a “values-to-action” journey. Drawing on the interface between transformational leadership and organizational culture, this study focused on the birth of the Severn Stars—a professional netball club in the United Kingdom. In particular, this PAAR investigation explored how the leader’s values were operationalized through the club’s inaugural year. Fourteen operational managers, coaches, and play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 46 publications
(87 reference statements)
0
0
0
Order By: Relevance
“…The findings in this section have demonstrated that whilst there are clear connections between the gears of Appropriate Settings and Quality Social Dynamics, most notably relating to the club structure and social environment, there are many elements which are not producing the frictionless movement which might see the gears turning more smoothly in this context. The power of the Superleague to act as an inspirational incentive was also reported by Navin et al (2020), and remains strongly in evidence in this second year of the club's operation. Navin et al (2020) also reported that investigating the roles and perceptions of a broader range of stakeholders would provide further insight into the club's overall connectivity.…”
Section: Connections Through Novas and To The Community (Community/le...supporting
confidence: 58%
See 4 more Smart Citations
“…The findings in this section have demonstrated that whilst there are clear connections between the gears of Appropriate Settings and Quality Social Dynamics, most notably relating to the club structure and social environment, there are many elements which are not producing the frictionless movement which might see the gears turning more smoothly in this context. The power of the Superleague to act as an inspirational incentive was also reported by Navin et al (2020), and remains strongly in evidence in this second year of the club's operation. Navin et al (2020) also reported that investigating the roles and perceptions of a broader range of stakeholders would provide further insight into the club's overall connectivity.…”
Section: Connections Through Novas and To The Community (Community/le...supporting
confidence: 58%
“…The power of the Superleague to act as an inspirational incentive was also reported by Navin et al (2020), and remains strongly in evidence in this second year of the club's operation. Navin et al (2020) also reported that investigating the roles and perceptions of a broader range of stakeholders would provide further insight into the club's overall connectivity.…”
Section: Connections Through Novas and To The Community (Community/le...supporting
confidence: 58%
See 3 more Smart Citations